1990
DOI: 10.1210/endo-127-3-1206
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Purification of Melatonin Receptors from Lizard Brain*

Abstract: Melatonin receptors in lizard brain were identified and characterized using 125I-labeled melatonin ([125I]MEL) after solubilization with the detergent digitonin. Saturation studies of solubilized material revealed a high affinity binding site, with an apparent equilibrium dissociation constant of 181 +/- 45 pM. Binding was reversible and inhibited by melatonin and closely related analogs, but not by serotonin or norepinephrine. Treatment of solubilized material with the non-hydrolyzable GTP analog, guanosine 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…These data indicate that the complex is relatively stable at 4 "C but at 37 "C the receptor complex dissociates irreversibly. This is in contrast to solubilized receptor complex isolated from the lizard brain, where 50% of the solubilized Fraction number 0 receptor complex can exchange cold melatonin for 12sI-Mel at 4 "C over a period of 16 h and the complex dissociates at 37 "C within 5 min (18). Activation of a G-protein coupled receptor results in the exchange of bound GDP for GTP at the guanine nucleotide binding site of the a-subunit of the G-protein complex.…”
Section: Properties Of the Solubilized P T Receptormentioning
confidence: 67%
See 1 more Smart Citation
“…These data indicate that the complex is relatively stable at 4 "C but at 37 "C the receptor complex dissociates irreversibly. This is in contrast to solubilized receptor complex isolated from the lizard brain, where 50% of the solubilized Fraction number 0 receptor complex can exchange cold melatonin for 12sI-Mel at 4 "C over a period of 16 h and the complex dissociates at 37 "C within 5 min (18). Activation of a G-protein coupled receptor results in the exchange of bound GDP for GTP at the guanine nucleotide binding site of the a-subunit of the G-protein complex.…”
Section: Properties Of the Solubilized P T Receptormentioning
confidence: 67%
“…Attempts to solubilize the melatonin receptor from brain tissue revealed the detergent digitonin at a concentration of 2% was effective in solubilizing 10-15% of receptors from the lizard brain. Furthermore, the receptor was required to be pre-bound by melatonin or a n analogue before solubilization and the receptor was released with its associated G-protein complex (18). Using 2% digitonin we have been able to release the melatonin receptor from the ovine PT membrane.…”
Section: Solubilization Of the Pt Melatonin Receptormentioning
confidence: 99%
“…High affinity binding sites have been detected by assays with crude membrane homogenates or in vitro autoradiography, in several tissues and organs . Among these, are the central nervous system of mammals, birds, reptiles and fish (Zisapel et al 1988;Rivkees et al 1989Rivkees et al , 1990Martinoli et al 1991;Ekstr6m and Vanecek 1992;Iigo et al 1994;Pang et al 1994a;Davies et al 1995) as well as the retina of some amphibians and birds (Dubocovich and Takahashi 1987;Wiechmann and Wirsig-Wiechmann 1991), the kidney (duck), spleen (birds and mammals) and heart (fish) (Yu et al 1991 ;Song et al 1992;Pang et al 1994b). Inhibition of melatonin binding by GTP and analogs suggested that the melatonin receptor is coupled to a GTP-binding protein (Morgan and Williams 1989;Morgan et al 1994), a conclusion supported by the recent cloning of the melatonin receptor from frog melanophores (Ebisawa et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…are the central nervous system of mammals, birds, reptiles and fish (5)(6)(7)(8)(9)(10)(11)(12)(13) as well as the retina of some amphibians and birds, mammals) (1). In most species, this control is mediated through circadian oscillators located within (e.g.…”
mentioning
confidence: 99%